Sistema fuzzy para estimativa do comportamento de pintinhos submetidos a diferentes intensidades e durações de exposição térmica na segunda semana de vida - Alcântara, Danielle Aparecida (2016)
The behavior of broiler chickens constitute a non-invasive form of evaluating the comfort conditions in relation to the thermal environment. Thus, we aimed at developing a fuzzy inference system for predicting the behavior of broiler chicken in function of the thermal environment and the duration of thermal exposure. Two hundred and forty broiler chicken, in the second week of life, were submitted to 4 air temperatures (tair : 24, 27, 30 and 33 o C) and 4 durations of thermal exposure DET: 1, 2, 3 and 4 days) in acclimatized wind tunnels. The behaviors, presence in the feeder (PF), presence in the drinking fountain (PD), grouping (G) and presence in intermediate areas (IA) were continuously evaluated (24 h day -1 ) between the 8 th and 11 th day of life. A fuzzy interference system was developed to predict PF, PD, G and IA in function of t air ( o C) and DET (days). Triangular pertinence curves were used to represent the entry and output data. The Mamdani and gravity center methods were used for inference and defuzzification, respectively. The fuzzy inference was adequate for predicting the behavior (PF, PD, G and IA) of broiler chicken with ages ranging from 8 to 11 days.